Climate Information Services: Understand your climate - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This poster aims to enhance understanding of climate variability and its associated uncertainties. It is designed as a valuable tool and intended to be utilized by farmer support agencies to promote and disseminate essential climate services. Through visual depictions and explanations of fundamental climate concepts—such as distinguishing between weather and climate, understanding uncertainty and probability, and recognizing the impacts of El Niño and La Niña phenomena—the poster seeks to empower farmers and decision-makers to navigate the complexities of agricultural planning and operations under varying climatic conditions.